1999
DOI: 10.1080/07315724.1999.10718845
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ascorbic Acid Supplementation on the Blood Lead Levels of Smokers

Abstract: Daily supplementation with 1000 mg of ascorbic acid results in a significant decrease of blood-lead levels associated with the general population. Ascorbic acid supplementation may provide an economical and convenient method of reducing blood-lead levels, possibly by reducing the intestinal absorption of lead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 21 publications
0
35
0
1
Order By: Relevance
“…Interaction between lead and calcium can occur at several sites in the body, including cellular mechanisms that regulate ion transports across cell membrane, competition for these sites might hamper lead from entering into the cells (Pounds 1991). Dawson et al (1999) reported supplementation of 1000 mg ascorbic acid daily could result in a significant decrease of BLLs, however, urinary lead excretion showed little change, suggested its Mice in ''Untreated group'' was treated with no agent in addition to lead, so it was positive control; mice in ''DMSA alone'' treated with 50 mg/kg b.w DMSA; ''DMSA high'' treated with 100 mg/kg b.w DMSA; ''Ca + Vc'' treated with 400 mg/kg b.w calcium carbonate and 100 mg/kg b.w ascorbic acid; ''DMSA + Ca + Vc'' treated with 50 mg/kg b.w DMSA , 400 mg/ kg b.w calcium carbonate and 100 mg/kg b.w ascorbic acid. Mice in ''Control'' were not exposed to lead, it was negative control protective effects were due to the inhibition of intestinal absorption of lead.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction between lead and calcium can occur at several sites in the body, including cellular mechanisms that regulate ion transports across cell membrane, competition for these sites might hamper lead from entering into the cells (Pounds 1991). Dawson et al (1999) reported supplementation of 1000 mg ascorbic acid daily could result in a significant decrease of BLLs, however, urinary lead excretion showed little change, suggested its Mice in ''Untreated group'' was treated with no agent in addition to lead, so it was positive control; mice in ''DMSA alone'' treated with 50 mg/kg b.w DMSA; ''DMSA high'' treated with 100 mg/kg b.w DMSA; ''Ca + Vc'' treated with 400 mg/kg b.w calcium carbonate and 100 mg/kg b.w ascorbic acid; ''DMSA + Ca + Vc'' treated with 50 mg/kg b.w DMSA , 400 mg/ kg b.w calcium carbonate and 100 mg/kg b.w ascorbic acid. Mice in ''Control'' were not exposed to lead, it was negative control protective effects were due to the inhibition of intestinal absorption of lead.…”
Section: Discussionmentioning
confidence: 99%
“…Data on current diet were collected using a semiquantitative foodfrequency questionnaire (Willett et al 1985), which included questions on frequency of consumption of 61 foods and on the use of vitamins and mineral supplements. Food frequency data may be used to compute mean daily intake of vitamins and minerals, including vitamin C, calcium, and iron (in milligrams), each of which has been associated with blood or bone lead concentrations (Cheng et al 1998;Dawson et al 1999;Hernandez-Avila et al 1996;Willett 1990). The questionnaire has shown good reliability and validity related to recent nutrient intake (Willett 1990;Willett et al 1985).…”
mentioning
confidence: 99%
“…We began with an unadjusted model and then considered variables that were suspected to confound the lead-diagnosis association or were known to be associated with BPb (Cheng et al 1998;Dawson et al 1999;Hernandez-Avila et al 1996): age in years; sex; race (white vs. nonwhite); number of rooms in home; years of education; current cigarette smoker (yes vs. no); pack-years of smoking; reported daily consumptions of vitamin C, calcium, and iron; and ethanol use (heavy vs. light use). In the final model, we included a variable if in a univariate model either a) it was associated with the diagnosis (at p < 0.10) or b) it was associated with the BPb concentration (at p < 0.10).…”
mentioning
confidence: 99%
“…Studies with human subjects have also found that supplementation with vitamin C reduced lead levels (Dawson et al 1999). One study randomly assigned nonoccupationally exposed male smokers into three treatment groups (placebo N = 25, Vitamin C 200 mg daily N = 25, and vitamin C 1,000 mg daily N = 25).…”
Section: Ascorbic Acid (Vitamin C)mentioning
confidence: 99%
“…Baseline blood lead levels were low and similar to that reported by other studies of the general population. Supplementation with 1,000 mg of vitamin C (but not 200 mg) reduced blood lead levels by 81% (Dawson et al 1999). However, according to a literature review by Hsu and Guo (2002), the benefit of vitamin C supple mentation seems to be found most consistently in studies with subjects with lower lead levels.…”
Section: Ascorbic Acid (Vitamin C)mentioning
confidence: 99%